Investigation of Q-Switching Characteristics in Single- and Double-Spacing Multi-Wavelength Brillouin Erbium Fiber Laser - Tan, S.J.; Jusoh, Z.; Ali, N.M.; Arof, Hamzah; Ahmad, Harith; Harun, Sulaiman Wadi (Institute of Electrical and Electronics Engineers (IEEE), 2013)
A multi-wavelength Brillouin erbium fiber laser (BEFL) with a Q-switching characteristic is demonstrated using a piece of non-zero dispersion shifted fiber (NZ-DSF) as a Brillouin gain medium (BGM) in conjunction with relaxation oscillation technique. The performance of the multi-wavelength short pulse generation is investigated for two different BEFL configurations for single and double Brillouin spacing outputs. The Q-switched BEFL generates a pulse train with repetition rates of 10.36 and 20.41 kHz whose corresponding pulse widths are 13.21 and 3.84 μs for the single and double Brillouin spacing outputs, respectively. The self-starting pulses are obtained within a low 1480-nm pump power region at a slightly higher power than the lasing threshold power. This pulse laser based on stimulated Brillouin scattering (SBS) is fairly stable at room temperature.